Takes two to tango. (3rd March 2014) - Munipalle, Phanibhushana C; Luther, Alison; Blake, Sarah; Burt, Caroline
Abstract : A 17-year-old girl was admitted with acute abdominal pain, vomiting and a leucocytosis, and was initially thought to have appendicitis. She underwent laparoscopic appendicectomy, where the tip of the appendix was noted to be mildly inflamed and she was discharged home the day after surgery. Two days later, she re-presented with small bowel obstruction which was subsequently demonstrated to be due to ingestion of five magnetic beads. She required a laparotomy and small bowel resection to resolve the obstruction, but has since fully recovered. This case highlights the potential intestinal complications caused by the intake of magnetic objects, and based on a literature review a number of recommendations are made to guide clinicians when managing similar cases.